Afterglow Performance of Phenylenevinylene‐Based Semiconducting Polymer Nanoparticles Doped with Photosensitizers Containing Electron‐Withdrawing Groups - Shi, Ting‐Jiao; Wang, Dong‐Hui; Zhao, Xu; Chen, Li‐Jian; Yan, Xiu‐Ping (Chemistry : a European journal, 2024)
It is usually believed that doping with photosensitizers capable of generating singlet oxygen (1O2) plays a pivotal role in enhancing the afterglow performance of semiconducting polymer nanoparticles (SPNs). However, the effect of doping photosensitizer bearing electron‐withdrawing groups has not been reported. Here we report the effect of doping with six photosensitizers possessing different electron‐withdrawing groups on the afterglow performance of SPNs using poly[(9,9‐di(2‐ethylhexyl)‐9H‐fluo‐rene‐2,7‐vinylene)‐co‐(1‐methoxy‐4‐(2‐ethylhexyloxy)‐2,5‐phenylenevinylene)] (PF‐MEHPPV) as substrate. It was found that the afterglow performance of SPNs was significantly influenced by doping with photosensitizers bearing electron‐withdrawing groups. For the doped photosensitizers with strong electron‐withdrawing groups, the stronger the electron‐withdrawing ability of the group, the worse of the afterglow performance of the SPN regardless of the 1O2 generation ability of the photosensitizer. When the doped photosensitizer exhibited weak or none electron‐withdrawing effect, the 1O2 generation ability of the photosensitizer played a dominant role on the afterglow performance of the SPNs. This work deepens the understanding of the design and synthesis of SPNs with different afterglow properties. For the doped photosensitizers with strong electron‐withdrawing groups, the stronger the electron‐withdrawing ability of the group, the worse of the afterglow performance of the SPN regardless of the 1O2 generation ability of the photosensitizer. When the doped photosensitizer exhibited weak or none electron‐withdrawing effect, the 1O2 generation ability of the photosensitizer played a dominant role on the afterglow performance of the SPNs.